Validity of Accelerometry to Measure Physical Activity Intensity in Children with an Acquired Brain Injury - Baque, E.; Sakzewski, L.; Trost, S.; Boyd, Roslyn; Barber, L. (Lippincott Williams & Wilkins, Inc., 2017)
© 2017 Wolters Kluwer Health, Inc. and Academy of Pediatric Physical Therapy of the American Physical Therapy Association. Purpose: To evaluate the validity of the ActiGraph accelerometer (AG) to differentiate between standardized, physical activity tasks using oxygen consumption (o 2) as the criterion measure in children and adolescents with an acquired brain injury; to determine vector magnitude activity intensity cut-points; to compare performance of cut-points to previously published cut-points. Methods: Twenty-seven children performed standardized walking and stepping activities wearing a portable indirect calorimeter, AG, and heart rate monitor. Differences in o 2 and AG vector magnitude activity counts were measured during activities. Receiver operating characteristic curves were determined for intensity cut-points. Results: o 2 and AG activity counts significantly increased as walking speed increased. Discrimination of the newly derived cut-points was excellent and demonstrated greater agreement compared with the previously published cut-points. Conclusion: Output from accelerometers can differentiate physical activity intensity in children with an acquired brain injury. Future studies can apply these cut-points to evaluate physical activity performance.